(untitled) (Emergency Care Journal, 2019)
Mondini-like dysplasia is a rare congenital inner ear malformation (IEM) and the most common anomaly associated with recurrent bacterial meningitis in children. Early diagnosis of Mondinilike dysplasia is crucial for preventing recurrent bacterial meningitis. We report a case of a 15-year-old girl with unrecognized Mondini-like dysplasia that was early diagnosed in the Emergency Department at the first episode of bacterial meningitis. Assessing hearing function in children who have their first episode of meningitis is crucial. Abnormal hearing test results are critical diagnostic findings that help to suspect an IEM. In addition, high-resolution computed tomography of the temporal bones is an excellent diagnostic tool for IEM.